Entomology glossary - Prasad, T.V. (New Delhi : New Vishal Publications)
Entomology glossary is a collection of terminology of Entomology. this book consists of description of various terms associated with Entomology dealing with both the basic and applied aspects of Entomology enriched with recent advances. This book consists of different terms on the various topics like systematics, taxonomy, morphology, physiology, ecology,biological control, toxicology, pesticides application equipments, pesticides, host plant resistance, innovative approaches in pest control, integrated pest management, insect pests of crops, stored product Entomology, beneficial insects and pests of medical importance. Most of the information was pooled and presented in a comprehensive and lucid manner for easy reading and understanding. This book serve as a ready reference to understand the various terms associated with Entomology in simple and comprehensive manner.
Keywords: Entomology -- Dictionary